Are We Spending Wisely? Impact of POSNA Grants on Scholarly Productivity and Future Funding Success. Issue 1 (January 2019) - Nhan, Derek T.; Schoenecker, Jonathan G.; Larson, A. Noelle; Sponseller, Paul D.
Abstract : Background: The Pediatric Orthopaedic Society of North America (POSNA) funds grants to improve pediatric musculoskeletal care and maximize new knowledge through publications, presentations, and further funding. We assessed the productivity of POSNA grants by number and rate of grant-specific publications, citations, and extramural funding; determined whether project type or completion status was associated with extramural funding; and compared the success of POSNA-funded versus all other podium presentations by publication rate and POSNA awards. Methods: We reviewed final reports for all 85 POSNA grants from 2003 to 2014. To determine grant productivity, we assessed the publication, presentation, and extramural funding rates, and the percentage of grants that achieved at least 1 scholarly output (publication or presentation). Citation counts were determined within 3 years after publication. Results: Overall, each grant achieved ~1.53 publications and 15.4 citations. Thirty-three percent secured extramural funding. However, 25% of grants could not be tracked to a scholarly product. Projects that reached completion and were of the basic science type (compared with clinical) were more likely to receive extramural funding. Compared with all other podiums, a greater proportion of POSNA-funded presentations led to a publication (64% vs. 48%, respectively; P =0.02) and were more likely to receive a POSNA award. Approximately 52% of funded projects were not presented at POSNA meetings. Conclusions: Although most POSNA-funded projects led to scholarly output, 25% of them produced no publications or podium presentations. POSNA-funded projects were more likely to lead to a publication and to have a higher chance of winning a POSNA award compared with all other projects. The POSNA grant process is effective at identifying impactful research, but continued process improvement, such as a prospectively maintained database of grant recipient productivity and improved tracking of grant submission histories, are both in development as the first steps to improve accountability of grant recipients in translating their projects to scholarly products.